Technology Acceptance Model and Customer Experience in Enhancing Customer Satisfaction and Loyalty in Multichannel Marketing - Septiadinur Rejeki; Budi Setiawan; Riyanti Isaskar (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
Changes in consumer behavior in shopping, increasingly driven by digital technology, have impacted many retail businesses, including Omah Sayur, which developed multichannel marketing through both physical and online stores. Despite having six offline store branches and an online presence via social media and shopping apps, Omah Sayur faces challenges such as higher prices compared to competitors, inadequate service, and a manual cashier system. This study aims to analyze the effect of technology acceptance on customer experience, satisfaction, and loyalty; as well as formulate an effective multichannel marketing strategy. Using a quantitative approach and descriptive statistics, the study involved 60 female respondents with experience in both offline and online shopping. The results show that technology acceptance positively influences experience, satisfaction, and loyalty, although it does not significantly affect customer loyalty due to limited features in online shopping. Customer experience positively impacts satisfaction and loyalty, and influences loyalty through consumer satisfaction. Positive sensory, emotional, and social experiences enhance satisfaction and loyalty, which in turn encourages repurchase and word of mouth. A multichannel marketing strategy that prioritizes good customer experience is key to increasing customer loyalty at Omah Sayur.